Use of extensigraph in the examination of wheat flours - Boros, Norbert; Borbélyné Varga, Mária; Győri, Zoltán (Acta Agraria Debreceniensis, 2008)
The extensograph is widely used in quality control and research laboratories studying wheat flour quality. The most commonly used measurements include Rm, the maximum resistance (maximum height of the curve); R5 the resistance at a constant extension of 5 cm; E, extensibility (total curve length); Rm/E, the ratio of maximum resistance to extension; and A, the area under curve. The extensograph has proved useful in the classification and assessment of flours on the physical dough properties. Another important application is its use in wheat breeding programs. Furthermore, extensograph is an excellent tool to study the effects of a wide range of ingredients on dough properties of wheat flour (like oxidants, enzymes, salt and additives), and it can also be used measure the changes during the frozen storage. In the present study we provide a review of the scientific literature concerning the possible applications of the extensograph.